MEMBANGUN DESA BERKELANJUTAN MELALUI KERJA SAMA UNIVERSITAS DAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA BERBASIS MASYARAKAT DI DESA MANURUNGE KAB. BONE - Syamsuriadi, Syamsuriadi; A, Arisal (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2026)
One of the most appropriate approaches to use in building a sustainable village through community-based tourism development in Manurunge Village, Ulaweng District, Bone Regency, is the Participatory Action Research (PAR) approach, because this method will foster community participation in understanding and identifying the problems they face, analyzing them, planning solutions together, then organizing existing resources, carrying out various actions for change, and conducting evaluation and reflection on their performance outcomes, thereby creating knowledge to build a sustainable village through community-based tourism development.The results of this community service activity have been able to change the status quo of village government officials and the community, who still maintained old behaviors resistant to tourism development. This change was made possible through an appropriate approach using Focus Group Discussions to provide understanding and awareness about the urgency of sustainable village development through collaboration between universities and the community in community-based tourism development. This can be achieved by presenting information on the difference between the expected behavior and the behavior actually practiced, enabling them to consciously and actively engage in analyzing, planning, organizing, implementing, and evaluating the results of their joint work. Furthermore, this community service activity has been able to bring new behavioral patterns of the community into interventions within the structure to build new behaviors, values, and attitudes in the organizational process, as the village government apparatus has programmed in the RPJMDES for a tourism development package in 2024 in Manurunge Village, and with the existence of the village institution, namely BUMDes, as the tourism manager. Additionally, this community service activity has been able to stabilize the village government organization and village institution (BUMDes) in a new equilibrium condition, with the formation of supporting mechanisms, namely norms, policies, and organizational structures to support sustainable village development through cooperation between the University and the Community in the development of community-based tourism villages